Exploring the Possible Influence of Postmodernism on Adult Education - Anindya Sen (Akademik İncelemeler Dergisi)
In this paper, I look at the possible influences of postmodernism on the field of Adult Education (AE). In order to do that, I discuss the basic tenets of postmodernism (along with its origins as a reaction to modernity). I then look at various aspects of current AE theory and praxis and analyze how they have similarities to the basic ideas that underlie postmodern thought. The main conclusion of the paper is that there is strong evidence to believe that postmodernism has had a significant influence on current AE theory and praxis.